(untitled) (Bangladesh Medical Journal, 2023)
The incidence of antibiotic-resistant sepsis in children, particularly multidrug-resistant (MDR) sepsis, is increasing day by day. The aim of this study is to describe the pattern of antimicrobial resistance amongst pathogens isolated from blood sepsis of children. This descriptive type of cross-sectional study was carried out in the Microbiology Section of the Popular Diagnostic Centre, Sylhet from April to October 2021. Data were collected from the data record software at centre. All the blood culture positive reports of children of age 0-120 months were collected and antibiotic sensitivity tests were done to identify different organisms. Patients with incomplete data were excluded from this study. A total of 83 patient reports were appraised and data were analyzed by Statistical Package for Social Sciences (SPSS) software version 22. According to the reports majority of the children (59%) were male and male female ratio was 1.4:1. Mean age of the children was 16.54±26.4 months (Mean±SD). About one third (33%) of children were within 1 month, 60 % were between 31 to 60 days, and 7.2% within more than 60 days. Most frequent (72.3%) organisms were gram positive, among them nearly half (49.4%) of the organisms were Staphylococcus aureus. More than one fourth (27.7%) of the organisms were gram negative, among them E. Coli was common organism and found in 15.7% of the cultures specimen of children. Here we found Azithromycin, Ceftazidime, Ceftriaxone and Colistin were resistant in most of the gram-positive cases and in gram-negative cases most of the antibiotic were resistant, where Ceftazidime was resistant in all cases. Nearly two-third (64%) of the organisms were multidrug resistant (MDR), 6% were extensively drug-resistant (XDR) and none were pan-drug resistant. About 61% Staphylococcus spp, 77% of E. coli, 43% of Klebsiella were MDR. The majority of sepsis in children are MDR, with Staphylococcus spp. and E. coli being the most common organism. Anti-microbial resistance surveillance and farther large scale studies are now crucial to revise the National Antibiotic Guideline. Bangladesh Med J. 2022 May; 51(2): 30-36